PERLINDUNGAN HAK CIPTA MOTIF KAIN NAGE BELIMBUR KHAS KABUPATEN KETAPANG SEBAGAI EKSPRESI BUDAYA TRADISIONAL - NIM: A1011191238, PUTRI WAHYUNI (Jurnal Fatwa Hukum, 2024)
Abstract  Cultural works include parts of a creation that are protected by law, one of which is included in Traditional Cultural Expressions. One form of traditional cultural expression is the Nage Belimbur Cloth Typical of Ketapang Regency. The Nage Belimbur Motif Cloth Typical of Ketapang Regency has been around for a long time since the time of the Ketapang kingdom.The method used in this research is an empirical method by collecting primary data in the form of interviews. In this research, the author uses the Empirical method, which is a legal research method that is observed in the form of speech, writing, and/or behavior that can be observed from an individual, group, society, and/or a particular organization which is studied from a complete point of view, with a descriptive approach, namely by describing and analyzing based on existing facts or data collected as they were at the time this research was conducted.The typical Nage Belimbur cloth motif from Ketapang Regency is the result of traditional culture. Based on Law Number 28 of 2014 concerning Copyright, namely Article 38 concerning traditional cultural expressions, it is held by the state. Based on Article 40 UUHC, the forms of creation that are protected are creations in the fields of science, art and literature, including works of art with batik or other motifs. The Regional Government's efforts to protect the Nage Belimbur cloth motif have not yet carried out copyright registration for the cloth motif, because until now there is no Regional Regulation that regulates and protects the design of the Nage Belimbur cloth motif typical of Ketapang Regency. Registration of Copyright for EBT and registration of Intellectual Property is very important in order to obtain legal protection and prevent harmful practices.  Keywords: Protection; Fabric Motifs; Ketapang RegencyAbstract  Karya budaya termasuk bagian dari suatu ciptaan yang dilindungi oleh hukum salah satunya termasuk ke dalam Ekspresi Budaya Tradisional. Salah satu wujud dari Ekpresi budaya tradisional adalah Kain Nage Belimbur Khas Kabupaten Ketapang. Kain Motif Nage Belimbur Khas Kabupaten Ketapang sudah lama adanya sejak zaman kerajaan Ketapang.Metode yang digunakan dalam penelitian ini adalah metode empiris dengan mengumpulkan data-data primer berupa wawancara. Dalam penelitian ini penulis menggunakan metode Empiris adalah suatu metode penelitian hukum yang diamati berupa ucapan, tulisan, dan atau perilaku yang dapat diamati dari suatu individu, kelompok, masyarakat, dan atau organisasi tertentu yang dikaji dari sudut pandang yang utuh, dengan pendekatan Deskriptif, yaitu dengan menggambarkan dan menganalisa berdasarkan fakta atau data yang ada yang terkumpul sebagaimana adanya pada saat penelitian ini dilakukan.Motif kain Nage Belimbur Khas dari Kabupaten Ketapang merupakan hasil dari budaya tradisional. Berdasatkan Undang-undang Nomor 28 tahun 2014 Tentang Hak Cipta yaitu Pasal 38 mengenai ekpresi budaya tradisional dipegang oleh negara. Berdasarkan Pasal 40 UUHC, bentuk-bentuk ciptaan yang dilindunhi ialah ciptaan dibidang ilmu pengetahuan, seni, dan sastra, termasuk didalamnya yaitu karya seni batik atau motif lain. Upaya perlindungan Pemerintah Daerah terhadap Motif kain Nage Belimbur belum dilakukan pendaftarannya Hak Cipta atas motif kain tersebut, karena hingga saat ini belum ada Peraturan Daerah yangmengatur dan melindungi desain Motif kain Nage Belimbur Khas Kabupaten Ketapang. Pencatatan Hak Cipta atas EBT dan pendaftaran Kekayaan Intelektual sangatlah penting agar mendapatkan perlindungan Hukum dan mencegah praktik yang merugikan.  Kata Kunci: Perlindungan; Motif Kain; Kabupaten Ketapang